Implementasi Studi Numerasi pada Pembelajaran Matematika pada Kelas V di SDN Dukuhan Kerten Surakarta Tahun Pelajaran 2023/2024 - Parwisagita, Irine Prasanti; Daryanto, Joko; Kurniawan, Sandra Bayu (Didaktika Dwija Indria, 2026)
This study focuses on the role of teachers in mathematics learning that is adjusted to the four things that must be involved in numeracy associated with the mathematics learning module for grade V at SD Negeri Dukuhan Kerten Surakarta during the 2023/2024 academic year. This study involves the numeracy aspect, namely students can think critically and reason mathematically, connect mathematics learning with the surrounding environment, there is mathematical communication during learning, and mathematics learning that uses technological skills. This study focuses on the four things that must be included in the mathematics learning module. This study uses a descriptive qualitative method using a case study approach. Data collected through interviews, observations, and case studies. The fifth grade teacher of SD Negeri Dukuhan Kerten has taught numeracy studies in accordance with the elements of numeracy according to the Organisation Economic Co-Operation and Development (OECD) starting from students being able to think critically to the use of technology in learning. So it can be seen that the implementation of numeracy studies in grade V of SD Negeri Dukuhan Kerten Surakarta has been carried out in accordance with the elements of numeracy studies.